Analisis Pengaruh Kemudahan Penggunaan Financial Technology, Literasi Investasi, Dan Intensitas Penggunaan Aplikasi Keuangan Digital Terhadap Perilaku Investasi - Ni Desak Made Dwika Pandya Anggira Nata; Fadilla Purwitasari (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
The development of Financial Technology (fintech) has transformed the way people, particularly young generations, access financial services and engage in investment activities. This study aims to analyze the effects of Financial Technology ease of use, investment literacy, and the intensity of digital financial application usage on the investment behavior of Accounting students at Wijaya Kusuma University Surabaya. A quantitative approach with a causal research design was employed. Primary data were collected through questionnaires distributed to 108 students who had used digital investment applications. Purposive sampling was applied, and the data were analyzed using multiple linear regression with SPSS version 26. The results indicate that the ease of use of Financial Technology has a positive and significant effect on investment behavior (β = 0.332; p = 0.000), investment literacy has a positive and significant effect on investment behavior (β = 0.295; p = 0.001), and the intensity of digital financial application usage has a positive and significant effect on investment behavior (β = 0.278; p = 0.002). Among the independent variables, the ease of use of Financial Technology is the most dominant factor influencing students’ investment behavior. The Adjusted R Square value of 0.634 indicates that the three independent variables explain 63.4% of the variance in investment behavior, while the remaining 36.6% is explained by other factors outside the research model. This study provides empirical evidence supporting the Technology Acceptance Model (TAM), Human Capital Theory, and Behavioral Finance Theory in explaining students’ investment behavior in the digital transformation era. The findings are expected to provide insights for universities, fintech service providers, and regulators in enhancing investment literacy and optimizing digital financial services to encourage greater investment participation among young generations.